Prognostic utility of biopsy‐derived cell cycle progression score in patients with National Comprehensive Cancer Network low‐risk prostate cancer undergoing radical prostatectomy: implications for treatment guidance. (11th June 2017) - Tosoian, Jeffrey J.; Chappidi, Meera R.; Bishoff, Jay T.; Freedland, Stephen J.; Reid, Julia; Brawer, Michael; Stone, Steven; Schlomm, Thorsten; Ross, Ashley E.
Abstract : Objectives: To determine the prognostic utility of the cell cycle progression (CCP) score in men with National Comprehensive Cancer Network (NCCN)‐defined low‐risk prostate cancer (PCa) undergoing radical prostatectomy (RP). Patients and Methods: Men who underwent RP for Gleason score ≤6 PCa at three institutions (Martini Clinic [MC], Durham Veterans Affairs Medical Center [DVA] and Intermountain Healthcare [IH]) were identified. The CCP score was obtained from diagnostic (DVA, IH) or simulated biopsies (MC). The primary outcome was biochemical recurrence (BCR; prostate‐specific antigen ≥0.2 ng/mL) after RP. The prognostic utility of the CCP score was assessed using Kaplan–Meier analysis and multivariable Cox proportional hazards models in the subset of men meeting NCCN low‐risk criteria and in the overall cohort. Results: Among the 236 men identified, 80% (188/236) met the NCCN low‐risk criteria. Five‐year BCR‐free survival for the low (<0), intermediate (0–1) and high (>1) CCP score groups was 89.2%, 80.4%, 64.7%, respectively, in the low‐risk cohort ( P = 0.03), and 85.9%, 79.1%, 63.1%, respectively, in the overall cohort ( P = 0.041). In multivariable models adjusting for clinical and pathological variables with the Cancer of the Prostate Risk Assessment (CAPRA) score, the CCP score was an independent predictor of BCR in the low‐risk (hazard ratio [HR] 1.77 per unit score, 95% confidence interval [CI] 1.21, 2.58; P = 0.003) and overall cohorts (HR 1.41 per unit score, 95% CI 1.02, 1.96; P = 0.039). Conclusion: In a cohort of men with NCCN‐defined low‐risk PCa, the CCP score improved clinical risk stratification of men who were at increased risk of BCR, which suggests the CCP score could improve the assessment of candidacy for active surveillance and guide optimum treatment selection in these patients with otherwise similar clinical characteristics.